Treatment of Jaundice using Blue LED Strips as a Light Source - Wan Mohamed Rizal, Wan Nur Aleez (2017)
Jaundice is a condition that causes yellow discolouration of the skin and sclera as a result of high bilirubin concentration in the body and the most opted treatment is phototherapy as it is the most conventional and reliable treatment. LEDs are preferable as the light source in phototherapy rather than fluorescent lamps and halogen lamps because it generate less heat. This paper focuses on using blue LED as a light source to expose the food colouring solution which represents bilirubin concentration. The distances that are varied in this experiment is the distance between each blue LED and the distance between blue LED and food colouring solution. Spectrophotometer is used to measure the absorption of the food colouring solution. The results of the experiment shows that the closer the distance between each blue LED and the closer the distance between blue LED and the food colouring solution, the higher the absorption reading of the food colouring solution.